Differences between α-linolenic and linoleic acid supplementation on the redox status and cardiodynamic parameters of male and female Wistar albino rats - Radoman, Kristina; Živković, Vladimir; Nikolić, Tamara; Stojić, Isidora; Raičević, Danijela; Jeremić, Jovana; Srejović, Ivan; Jakovljević, Vladimir (Archives of Biological Sciences, 2018)
The aim of present study was to investigate the difference between α-linolenic acid (ALA, omega-3) and linoleic acid (LA, n-6) on the redox status and cardiac function of the isolated rat heart. ALA or LA were administered for 6 weeks by gavage to all animals, which were randomly divided into 4 groups: male rats treated with a linoleic acid (M-LA), dose of 7.3 mg/kg/day; female rats treated with a linoleic acid (F-LA), dose of 7.3 mg/kg/day; male rats treated with an α-linolenic acid (M-ALA), dose of 165 mg/kg/day; female rats treated with α-linolenic acid (F-ALA), dose of 165 mg/kg/day. Using the Langendorff technique, markers of heart function were evaluated: the maximum and minimum rates of pressure development in the left ventricle (LV; dp/dt max, dp/dt min), systolic and diastolic left ventricle pressure (SLVP, DLVP, respectively), heart rate (HR) and coronary flow (CF). We measured the concentrations of prooxidative markers: nitrites (NO2-), superoxide anion radicals (O2-) and hydrogen peroxide (H2O2), as well as the index of lipid peroxidation (TBARS) in the plasma and effluent. In the lysate, we measured the concentrations of reduced glutathione (GSH), catalase (CAT) and superoxide dismutase (SOD). ALA more negatively influenced the isolated rat heart, especially in females. In contrast, the administration of LA was linked to more prominent oxidative stress, while the application of ALA was associated with improved activity of the antioxidative defense system (with better values in males). https://doi.org/10.2298/ABS170810038R Received: August 10, 2017; Revised: September 24, 2017; Accepted: October 6, 2017; Published online: October 16, 2017 How to cite this article: Radoman K, Živković V, Nikolić T, Stojić I, Raičević D, Jeremić J, Srejović I, Jakovljević V. Differences between α-linolenic and linoleic acid supplementation on the redox status and cardiodynamic parameters of male and female Wistar albino rats. Arch Bio Sci. 2018;70(2):223-31.